Reading, desire, and the Eucharist in early modern religious poetry - Netzley, Ryan, 1972- (Toronto [Ont.] : University of Toronto Press, 2011)
"The courtly love tradition had a great influence on the themes of religious poetry - just as an absent beloved could be longed for passionately, so too could a distant God be the subject of desire. But when authors began to perceive God as immanently available, did the nature and interpretation of devotional verse change? Ryan Netzley argues that early modern religious lyrics presented both desire and reading as free, loving activities, rather than as endless struggles or dramatic quests.
Reading, Desire, and the Eucharist analyzes the work of prominent early modern writers - including John Milton, Richard Crashaw, John Donne, and George Herbert - whose religious poetry presented parallels between sacramental desire and the act of understanding written texts. Netzley finds that by directing devotees to crave spiritual rather than worldly goods, these poets questioned ideas not only of what people should desire, but also how they should engage in the act of yearning. Challenging fundamental assumptions of literary criticism, Reading, Desire, and the Eucharist shows how poetry can encourage love for its own sake, rather than in the hopes of salvation."--Pub. desc.
Take and Taste, Take and Read: Desiring, Reading, and Taking Presence in George Herbert's The Temple -- Reading Indistinction: Desire, Indistinguishability, and Metonymic Reading in Richard Crashaw's Religious Lyrics -- Loving Fear: Affirmative Anxiety in John Donne's Divine Poems -- Desiring What Has Already Happened: Reading Prolepsis and Immanence in John Milton's Early Poems and Paradise Regained.
Includes bibliographical references and index.
Keywords: Christian poetry, English -- Early modern, 1500-1700 -- History and criticism; Christianity and literature -- England -- History -- 17th century; Lord's Supper in literature; God in literature; POETRY / English, Irish, Scottish, Welsh; Electronic books